2016
DOI: 10.1007/s12192-015-0651-7
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin protects HCT116 cells from Dichlorvos-induced oxidative stress and apoptosis

Abstract: The present study was designed to assess the possible protective effects of Quercetin (QUER), a flavonoid with well-known pharmacological effects, against Dichlorvos (DDVP)-induced toxicity in vitro using HCT116 cells. The cytotoxicity was monitored by cell viability, reactive oxygen species (ROS) generation, anti-oxidant enzyme activities, malondialdehyde (MDA) production, and DNA fragmentation. The apoptosis was assessed through the measurement of the mitochondrial transmembrane potential (ΔΨm) and caspase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 45 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Intestinal absorption kinetic experiments in mouse intestinal cells in vivo and human intestinal cells in vitro showed that Que had good intestinal absorption efficiency [ 26 , 27 ]. Ben et al [ 28 ] reported that Que could protect the human colon cancer cell line, HCT116, from exposure to dichlorvos, inhibiting apoptosis by regulating the redox system in HCT116. However, there is not much detailed evidence to support whether or not Que promotes the proliferation of porcine small intestinal epithelial cells, and whether or not Que has any inhibitory effect on oxidative damage in porcine intestinal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal absorption kinetic experiments in mouse intestinal cells in vivo and human intestinal cells in vitro showed that Que had good intestinal absorption efficiency [ 26 , 27 ]. Ben et al [ 28 ] reported that Que could protect the human colon cancer cell line, HCT116, from exposure to dichlorvos, inhibiting apoptosis by regulating the redox system in HCT116. However, there is not much detailed evidence to support whether or not Que promotes the proliferation of porcine small intestinal epithelial cells, and whether or not Que has any inhibitory effect on oxidative damage in porcine intestinal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The use of medicinal plants for the treatment of diseases is gaining more popularity in the 21st century especially in Africa (Kayode & Kayode, ; Mahlangeni, Moodley, & Jonnalagadda, ) This is consequent on their various biologically active phytochemicals (Krishnaiah, Sarbatly, & Nithyanandam, ; Rahmatullah et al, ). Flavonoids mitigate free radical/oxidative stress induced tissue damage (Chen et al, ; Salem et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Qcn has been shown to play a fundamental role in modulating mitochondrial function by influencing ∆Ψm (Ben Salem et al, 2016 ). To determine whether Qcn also has an anti-apoptotic effect on hypoxia-induced RGC by ameliorating mitochondrial function, ∆Ψm and intracellular ROS levels were determined under hypoxia with or without Qcn.…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin (Qcn) is a natural and important dietary flavonoid compound that is widely distributed in fruits and vegetables. Mounting evidence suggests that Qcn has numerous beneficial effects, including anti-inflammatory (Periasamy et al, 2016 ), anti-apoptosis (Ben Salem et al, 2016 ), anti-ischemic (Ekinci Akdemir et al, 2016 ), anti-oxidation (Xu et al, 2016 ), anti-endoplasmic reticulum (ER) stress (Ben Salem et al, 2015 ), anti-mutagenic (Barcelos et al, 2011 ), and anti-viral (Wu W. et al, 2015 ) effects in addition to promoting mitochondrial biogenesis (Sharma et al, 2015 ). In the retina, it has been reported that Qcn has protective effects in multiple lesions, including retina ischemia-reperfusion injury (Arikan et al, 2015 ), oxidative damage of RPE cells (Hytti et al, 2015 ), diabetes-induced retinal neurodegeneration (Kumar et al, 2014 ), choroidal neovascularization in age-related macular degeneration (Zhuang et al, 2011 ), vascular endothelial growth factor-induced choroidal and retinal angiogenesis (Li et al, 2015 ), and ocular inflammation (Romero et al, 1989 ).…”
Section: Introductionmentioning
confidence: 99%